PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK. CABANG MANADO - Nelwan, Diandra Gabriela; Areros, William Agustinus; Tampi, Johny Revo Elia (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Abstract, PT. Bank Negara Indonesia (Persero), Tbk Branch Manado is one of the largest national banks in North Sulawesi and even Indonesia. For the PT. BNI (Persero) Tbk branch Manado viewed with keen market in Indonesia such as in the area of Manado one with a marketing strategy, especially the quality of services in order to achieve company goals. This became the basis for the author to raise the issue: "Is the Quality of Service effect on customer satisfaction at PT. BNI (Persero) Tbk Branch Manado? "The purpose of this study was to determine the effect of service quality ie reliability, responsiveness, assurance, empathy and tangible to customer satisfaction at PT. BNI (Persero) Tbk Branch Manado. In order to earn and maintain consumer need for a strategy that requires commitment, good and human resources that aim to make products that are offered in accordance with the wishes of consumers so as to give satisfaction.The method used is the analysis method for the quantitative description of the relationship which consists of a combination of variable reliability, responsiveness, assurance, empathy and tangible is the variable that is used to view customer satisfaction or customer. Application of the quality of service is a business marketing ataus Strategy in pasarsasaran to maintain customer loyalty. Analysis technique used is the method of Multiple Regression Analysis and Correlation is to determine the effect of service quality on customer satisfaction.Based on the results of this research is that simultaneously the reliability (X1), responsiveness (X2), Security (X3), Empathy (X4), and Tangible (X5) significant Impact on customer loyalty (Y). With a variable value that is intangible (X5) are the most positive and significant impact on customer satisfaction. So in creating customer satisfaction, the company should be able to increase the value and brand image. The better the customer ratings, the higher the satisfaction.Keywords : Reliability, Responsiveness , Assurance , Empathy , embodies and Customer Satisfaction